Pemberdayaan Kelompok Difabel “Argodadi Pinilih” Berbasis Usaha Tani Jamur - Istiyanti, Eni; Sarjiyah; Widiyantono, Didik (Warta LPM, 2023)
Disabled group "Argodadi Pinilih" has 40 active members. The COVID-19 pandemic has caused some members to lose their jobs. Members of the disabled group began to try to cultivate oyster mushrooms in their homes and they also carried out their own maintenance. Some “baglog” cannot grow mushrooms because the environment where the mushrooms grow does not meet the requirements. The problems faced by the disabled group "Argodadi Pinilih" are low quantity and quality of oyster mushrooms, limited skills in making processed food from mushrooms and mushroom marketing is still limited. The objectives of this community empowerment activity are (a) increasing the quantity and quality of mushroom production (b) improving skills in the manufacture of processed food made from mushrooms, (c) expanding the mushroom market share. The methods used in the implementation of empowerment activities are (a) counseling on oyster mushroom cultivation and marketing strategies (b) training on processing food from oyster mushrooms, (c) facilitation house of mushroom and baglog. The results of the empowerment show that the training, mentoring and facilitation of mushroom house and “baglog” can increase the quantity and quality of oyster mushroom production, improve the skills in making processed food from mushrooms and expand the market share of oyster mushrooms. The knowledge and skills of the disabled group members about mushroom farming and processing increased as evidenced by the pre-test score of 79.23 and post-test of 86.00 with an increase 8.54%.